Four souls ; Tracks [compact disc, unabridged] : (two novels) - Erdrich, Louise (Harper Audio, 2004)
From New York Times bestselling author Louise Erdrich comes a haunting novel that continues the rich and enthralling Ojibwe saga begun in her novel Tracks. After taking her mother<U+2019>s name, Four Souls, for strength, the strange and compelling Fleur Pillager walks from her Ojibwe reservation to the cities of Minneapolis and Saint Paul. She is seeking restitution from and revenge on the lumber baron who has stripped her tribe<U+2019>s land. But revenge is never simple, and her intentions are complicated by her dangerous compassion for the man who wronged her.